Corrosion-resistant container bag and preparation process thereof

By using recycled pellets, corrosion-resistant modified polypropylene and modified calcium sulfate whiskers in the main material layer of the container bag, and using polytetrafluoroethylene in the inner lining layer, the problem of the materials that are susceptible to corrosion in the high-corrosive environment of existing container bags is solved, and higher corrosion resistance and tensile strength are achieved.

CN119590037APending Publication Date: 2025-03-11NANTONG LIANRONG GRP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411788524.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

When existing corrosion-resistant container bags are used for a long time in a highly corrosive environment, the material is difficult to completely resist corrosion, and microcorrosion of the material may occur, affecting the strength and sealing of the container bags.

Method used

A corrosion-resistant container bag is used, and its main material layer is composed of recycled pellets, corrosion-resistant modified polypropylene and modified calcium sulfate whiskers. Polytetrafluoroethylene is used as the inner lining layer material to improve the stability of the molecular chain and the compatibility of the material through modification treatment.

Benefits of technology

It significantly improves the corrosion resistance and tensile strength of the container bag, and can maintain good working performance for a long time in a highly corrosive environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005174720940000111
    Figure BDA0005174720940000111
Patent Text Reader

Abstract

The invention relates to a corrosion-resistant container bag and a preparation process thereof, and relates to the technical field of packaging materials, the corrosion-resistant container bag comprises a main body material layer and a lining layer, the main body material layer is prepared from the following components in parts by mass: 20 to 30 parts of regenerated granules, 50 to 70 parts of corrosion-resistant modified polypropylene, 10 to 20 parts of modified calcium sulfate whisker, 3 to 6 parts of plasticizer, 0.5 to 1.5 parts of antioxidant and 1.5 to 2.5 parts of lubricant. The preparation process comprises the following steps: preparing shaping flat filaments, and weaving to obtain a main body material layer; coating an adhesive on the bonding surface of the main body material layer and the lining layer, extruding and bonding, and heating and curing to obtain a bonding material; and the attaching material is cut and sewn, and the corrosion-resistant container bag is obtained. The container bag has the effect of improving the corrosion resistance of the container bag, and the container bag has high strength and can keep good working performance for a long time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of packaging materials, and in particular to a corrosion-resistant container bag and a preparation process thereof. Background Art

[0002] As a common means of logistics and transportation, bulk bags are widely used in the chemical, food, and pharmaceutical industries. They are widely recognized and used because they can effectively protect the internal items from the external environment and have high carrying capacity and convenient loading and unloading performance. However, with the increasing requirements for bulk bags in industrial production, especially in environments with strong chemical corrosion, the existing bulk bag materials and structures can no longer meet the needs.

[0003] The manufacture of existing corrosion-resistant bulk bags adopts a variety of technical means. In terms of the selection of the main material, polypropylene (PP) is mostly used as the basis, and various anti-corrosion additives are added to modify it to enhance its tolerance to common corrosive substances. In terms of structural design, an inner lining layer is usually set inside the bag body. Commonly used inner lining materials include plastic films such as polyethylene (PE) and polyvinyl chloride (PVC). For highly corrosive substances, polytetrafluoroethylene (PTFE) films with stronger corrosion resistance will be selected.

[0004] Although the above methods have improved the corrosion resistance of bulk bags to a certain extent, they still face many challenges in practical applications. In particular, when bulk bags are used for a long time in a highly corrosive environment, the existing material system of bulk bags is difficult to completely resist corrosion, and microscopic corrosion of the material may occur, which in turn affects the strength and sealing of the bulk bags, so there is room for improvement. Summary of the invention

[0005] In order to improve the corrosion resistance of bulk bags, the present application provides a corrosion-resistant bulk bag and a preparation process thereof.

[0006] The present application provides a corrosion-resistant container bag and a preparation process thereof using the following technical solutions: In the first aspect, the present application provides a corrosion-resistant container bag, which adopts the following technical solution: A corrosion-resistant container bag comprises a main material layer and an inner lining layer, wherein the raw material for preparing the inner lining layer comprises polytetrafluoroethylene, and the raw material for preparing the main material layer comprises the following components in parts by mass: Recycled granules 20-30 parts Corrosion-resistant modified polypropylene 50-70 parts Modified calcium sulfate whisker 10-20 parts Plasticizer 3-6 parts Antioxidant 0.5-1.5 parts Lubricant 1.5-2.5 parts.

[0007] Polytetrafluoroethylene has a unique molecular structure, and its main chain is composed of carbon-fluorine bonds. The fluorine atom has high electronegativity and small atomic radius, and can tightly wrap the carbon atom to form a highly stable structure, effectively preventing corrosive substances from penetrating and contacting the materials in the bag, thereby improving the corrosion resistance of the container bag; after reasonable screening and treatment, the recycled granular material can provide basic structural support for the container bag, which is energy-saving and environmentally friendly; the corrosion-resistant modified polypropylene is modified to improve the stability of the molecular chain and the corrosion resistance of the main material layer; the modified calcium sulfate whisker has a high aspect ratio, high strength and high modulus. After modification, it has good compatibility and interfacial bonding with components such as polypropylene in the main material. When the container bag is stretched by external force, the modified calcium sulfate whisker can effectively transfer stress, bear part of the tension, and prevent the generation and expansion of cracks, and synergize with recycled granular materials, corrosion-resistant modified polypropylene, etc. to improve the tensile strength of the main material layer.

[0008] Preferably, the raw materials for preparing the recycled pellets include discarded bulk bags and ethylene-vinyl acetate copolymer.

[0009] The recycling of discarded bulk bags reduces resource waste and environmental pollution, and their fiber structure and chemical properties can be reused through processing; the vinyl acetate group in ethylene-vinyl acetate copolymer can change the flexibility and polarity of the copolymer molecular chain, improve the compatibility of recycled aggregates and the interaction between materials, thereby enhancing the internal stability of the main material layer, thereby improving the overall strength and durability of the bulk bag, and improving its corrosion resistance and tensile strength.

[0010] Preferably, the regenerated pellets are prepared by the following steps: The recycled bulk bags are sorted and selected, and the impurities are removed and then cut and crushed to obtain bulk bag fragments; the bulk bag fragments are washed and dehydrated, and then dried to obtain dry bulk bag fragments; the dry bulk bag fragments are extruded and melted, and filtered while being extruded and melted, and then granulated and formed to obtain preliminary recycled pellets; the preliminary recycled pellets and ethylene-vinyl acetate copolymer are mixed and kneaded, and then extruded and granulated to obtain recycled pellets.

[0011] The recycled granules prepared according to the above steps have good system compatibility, and the prepared container bags have good corrosion resistance and high tensile strength.

[0012] Preferably, the raw materials for preparing the corrosion-resistant modified polypropylene include polypropylene body, maleic anhydride and trifluoropropylmethylcyclotrisiloxane.

[0013] Maleic anhydride plays a bridging role, and the carbon-carbon double bonds in its molecules undergo free radical grafting reaction with the polypropylene molecular chain under the action of the initiator. The introduced anhydride groups, on the one hand, enhance the interaction between the polypropylene molecular chains and improve the tolerance to polar corrosive media, and on the other hand, create conditions for the subsequent reaction with trifluoropropylmethylcyclotrisiloxane; trifluoropropylmethylcyclotrisiloxane is connected to the polypropylene molecular chain by means of the reaction with the anhydride groups, and the silicon-oxygen bonds in the siloxane give polypropylene good heat resistance and weather resistance, and the fluorine atoms build a stable protective layer with their strong electronegativity; the three work synergistically to optimize the molecular structure and properties of polypropylene, enhance the intermolecular forces, and improve the corrosion resistance and tensile strength of the main material layer of the container bag.

[0014] Preferably, the mass ratio of the polypropylene body, maleic anhydride and trifluoropropylmethylcyclotrisiloxane is 1:0.03:(0.15-0.25).

[0015] The corrosion-resistant modified polypropylene prepared according to the above mass ratio has good corrosion resistance and tensile strength.

[0016] Preferably, the raw materials for preparing the modified calcium sulfate whiskers include pretreated calcium sulfate whiskers, rare earth-doped graphene and aniline.

[0017] Pretreated calcium sulfate whiskers have high strength and rigidity; rare earth doped graphene changes the electronic structure and physical and chemical properties of graphene by doping with rare earth elements, making it have better electrical conductivity, thermal conductivity and synergistic effects with other materials. The lamellar structure of graphene can be evenly dispersed on the surface of calcium sulfate whiskers to form a reinforced network, effectively improving the overall strength and toughness of the whiskers; aniline forms a polymer coating on the surface of the whiskers through polymerization reaction, which enhances the compatibility of the whiskers with other components in the main material layer. At the same time, its polymer structure can further fill the gaps between the whiskers and increase the interaction between the whiskers; the synergistic effect of the three enables the modified calcium sulfate whiskers to better bear external forces in the main material layer of the container bag, effectively prevent the generation and expansion of cracks, and enhance the overall strength of the main material layer, thereby improving the tensile strength of the container bag. Its toughening and reinforcement effect can reduce defects between molecules and help improve the corrosion resistance of the container bag.

[0018] Preferably, the raw materials for preparing the rare earth-doped graphene include graphene oxide, lanthanum nitrate, cerium nitrate and yttrium nitrate.

[0019] After lanthanum is doped into graphene oxide, its electronic structure characteristics can promote the optimization of graphene's π-π conjugated system and enhance the in-plane chemical bonding force of graphene, so that when it is combined with pretreated calcium sulfate whiskers to construct a reinforced network, it can efficiently transfer stress and significantly improve the strength of the modified calcium sulfate whiskers, thereby improving the tensile strength of the container bag. At the same time, this structural optimization gives graphene better chemical inertness, which can effectively prevent erosion in the face of corrosive media and improve the overall corrosion resistance of the container bag. Due to its variable valence characteristics, cerium can form a special electron transfer channel when doped in the graphene lattice, which not only enhances the conductivity of graphene, but also helps to disperse local stress. , improve the tensile strength of modified calcium sulfate whiskers and container bags, and can quickly consume corrosive substances such as free radicals in redox reactions, thereby improving corrosion resistance; the high charge density characteristics of yttrium can polarize the surrounding chemical bonds, strengthen the crystal structure of graphene, make the modified calcium sulfate whiskers more stable, and enhance the tensile strength of the container bag. At the same time, it also improves the physical barrier ability of graphene to corrosive substances and its synergistic anti-corrosion ability with other components, thereby improving the corrosion resistance of the container bag; the three rare earth elements work synergistically to effectively improve the comprehensive performance of rare earth-doped graphene, enhance the strength and stability of the main material layer of the container bag, thereby improving the tensile strength and corrosion resistance of the container bag.

[0020] Preferably, the rare earth-doped graphene is prepared by the following steps: The graphene oxide is dispersed in water, and a graphene dispersion is obtained after ultrasonic treatment; lanthanum nitrate, cerium nitrate and yttrium nitrate are dissolved in water to obtain a rare earth mixed liquid; under stirring conditions, the rare earth mixed liquid is added to the graphene dispersion to obtain a mixed dispersion; ascorbic acid is added to the mixed dispersion, the temperature is raised and stirred for reaction, after cooling, centrifugation is performed to obtain a precipitate, the precipitate is washed three times with water and ethanol respectively, the washed precipitate is vacuum dried, and the dried precipitate is ground to obtain rare earth-doped graphene.

[0021] The rare earth-doped graphene prepared according to the above steps can effectively improve the corrosion resistance and tensile strength of the container bag.

[0022] Preferably, the mass ratio of the pretreated calcium sulfate whiskers, rare earth-doped graphene and aniline is 1:0.1:(0.6-0.8).

[0023] The modified calcium sulfate whiskers prepared according to the above mass ratio have good system compatibility, can toughen and reinforce the main material layer, and improve the corrosion resistance and tensile strength of the container bag.

[0024] In the second aspect, the present application provides a preparation process of a corrosion-resistant container bag, which adopts the following technical solution: A preparation process of a corrosion-resistant container bag comprises the following steps: The recycled pellets, corrosion-resistant modified polypropylene and modified calcium sulfate whiskers are stirred and mixed, a plasticizer, an antioxidant and a lubricant are added, the speed is increased and the mixture is stirred and mixed to obtain a mixture; the mixture is granulated to obtain a mixed pellet; the mixed pellet is extruded into a sheet, cooled in water, and cut into flat wires after cooling, and the flat wires are stretched and heat-set to obtain a set flat wire; the set flat wires are woven to obtain a main material layer; The adhesive is applied to the bonding surface of the main material layer and the lining layer, and after extrusion bonding, the bonding is heated and cured to obtain a bonding material; the bonding material is cut and sewn to obtain a corrosion-resistant container bag.

[0025] The corrosion-resistant container bag prepared according to the above steps has good corrosion resistance and high tensile strength, and can maintain good working performance for a long time.

[0026] In summary, the present application includes at least one of the following beneficial technical effects: 1. Polytetrafluoroethylene has a unique molecular structure, and its main chain is composed of carbon-fluorine bonds. The fluorine atom has high electronegativity and small atomic radius, and can tightly wrap the carbon atom to form a highly stable structure, effectively preventing corrosive substances from penetrating and contacting the materials in the bag, and improving the corrosion resistance of the container bag; after reasonable screening and treatment, the recycled granular material can provide basic structural support for the container bag, which is energy-saving and environmentally friendly; the corrosion-resistant modified polypropylene is modified to improve the stability of the molecular chain and the corrosion resistance of the main material layer; the modified calcium sulfate whisker has a high aspect ratio, high strength and high modulus. After modification, it has good compatibility and interface bonding with components such as polypropylene in the main material. When the container bag is stretched by external force, the modified calcium sulfate whisker can effectively transfer stress, bear part of the tension, and prevent the generation and expansion of cracks. It synergizes with recycled granular materials, corrosion-resistant modified polypropylene, etc. to improve the tensile strength of the main material layer.

[0027] 2. Maleic anhydride plays a bridging role. The carbon-carbon double bonds in its molecules undergo free radical grafting reaction with the polypropylene molecular chain under the action of the initiator. The introduced anhydride groups, on the one hand, enhance the interaction between the polypropylene molecular chains and improve the tolerance to polar corrosive media. On the other hand, it creates conditions for the subsequent reaction with trifluoropropylmethylcyclotrisiloxane. Trifluoropropylmethylcyclotrisiloxane is connected to the polypropylene molecular chain by means of the reaction with the anhydride groups. The silicon-oxygen bonds in the siloxane give polypropylene good heat resistance and weather resistance, and the fluorine atoms build a stable protective layer with their strong electronegativity. The three work synergistically to optimize the molecular structure and properties of polypropylene, enhance the intermolecular forces, and improve the corrosion resistance and tensile strength of the main material layer of the container bag.

[0028] 3. The pretreated calcium sulfate whiskers have high strength and rigidity; rare earth doped graphene changes the electronic structure and physical and chemical properties of graphene by doping with rare earth elements, making it have better electrical conductivity, thermal conductivity and synergistic effects with other materials. The lamellar structure of graphene can be evenly dispersed on the surface of calcium sulfate whiskers to form a reinforced network, effectively improving the overall strength and toughness of the whiskers; aniline forms a polymer coating on the surface of the whiskers through polymerization reaction, which enhances the compatibility of the whiskers with other components in the main material layer. At the same time, its polymer structure can further fill the gaps between the whiskers and increase the interaction between the whiskers; the synergistic effect of the three enables the modified calcium sulfate whiskers to better bear external forces in the main material layer of the container bag, effectively prevent the generation and expansion of cracks, and enhance the overall strength of the main material layer, thereby improving the tensile strength of the container bag. Its toughening and reinforcement effect can reduce the defects between molecules and help improve the corrosion resistance of the container bag. DETAILED DESCRIPTION

[0029] The present application discloses a corrosion-resistant container bag and a preparation process thereof. The raw materials used in the present application can be obtained from commercially available raw materials unless otherwise specified. The present application is further described in detail below in conjunction with the embodiments: Raw materials description: Ethylene-vinyl acetate copolymer model is DuPont EVAC250, polypropylene (CAS No.: 9003-07-0), molecular weight is 300,000, maleic anhydride (CAS No.: 108-31-6), trifluoropropylmethylcyclotrisiloxane (CAS No.: 2374-14-3), initiator is diisopropyl peroxide (CAS No.: 80-43-3), graphene oxide number is XFSG01, purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd., ascorbic acid (CAS No.: 50-81-7), sulfur Calcium acid whisker (CAS No.: 10101-41-4), aspect ratio of 70, γ-aminopropyltriethoxysilane (CAS No.: 919-30-2), aniline (CAS No.: 62-53-3), azobisisobutyronitrile (CAS No.: 78-67-1), plasticizer is dioctyl phthalate (CAS No.: 117-81-7), antioxidant is antioxidant 1010 (CAS No.: 6683-19-8), lubricant is calcium stearate (CAS No.: 1592-23-0), and the lining layer is polytetrafluoroethylene film.

[0030] Example 1 Preparation of recycled pellets: The recycled bulk bags are sorted and selected, and then cut and crushed after removing impurities to obtain bulk bag fragments; the bulk bag fragments are soaked and washed in water for 1 hour, and then centrifuged and dehydrated for 15 minutes at a centrifugal speed of 1200rpm. After centrifugation, they are dried at 60°C until the water content is less than 0.5% to obtain dry bulk bag fragments; the dried bulk bag fragments are conveyed to a twin-screw extruder for extrusion and melting, and the temperatures of each section in the extruder are 160-180°C for zone one, 180-200°C for zone two, 200-220°C for zone three, and 220-230°C for zone four. -240℃, filter through a 100-mesh stainless steel filter while extruding and melting, and after filtration, use an underwater pelletizer to granulate and form, the water temperature of the pelletizer is 30℃, and preliminary recycled pellets are obtained; the preliminary recycled pellets and ethylene-vinyl acetate copolymer are added into an internal mixer in a mass ratio of 4:1 for mixing and internal mixing, the temperature of the internal mixer is 200℃, the internal mixing time is 10min, the rotation speed is 50rpm, the material after internal mixing is extruded and granulated through a single screw extruder, the extruder temperature is 170-190℃, and recycled pellets are obtained.

[0031] Preparation of corrosion-resistant modified polypropylene 84.75 kg of polypropylene, 2.54 kg of maleic anhydride and 12.71 kg of trifluoropropylmethylcyclotrisiloxane were premixed in a high-speed mixer for 10 minutes at a premixing speed of 1000 rpm to obtain a premix; under a nitrogen atmosphere, the premix was added to an internal mixer, preheated at 180° C. at a speed of 50 rpm for 10 minutes, 0.5 kg of initiator was added, internal mixing was performed for 20 minutes, and the material was discharged to obtain corrosion-resistant modified polypropylene.

[0032] Preparation of modified barium sulfate whiskers 2 kg of graphene oxide was dispersed in 5 L of deionized water, and a graphene dispersion was obtained after ultrasonic treatment for 30 min; 0.1 kg of lanthanum nitrate, 0.05 kg of cerium nitrate and 0.05 kg of yttrium nitrate were dissolved in 1 L of deionized water to obtain a rare earth mixed solution; under the condition of stirring at a speed of 200 rpm, the rare earth mixed solution was added to the graphene dispersion, and the addition was completed within 1 hour. After the addition was completed, a mixed dispersion was obtained; 0.15 kg of ascorbic acid was added to the mixed dispersion, the temperature was raised to 100 ° C and stirred at a speed of 200 rpm for 4 hours, after cooling to below 30 ° C, centrifuged to obtain a precipitate, the precipitate was washed three times with deionized water and ethanol respectively, the washed precipitate was vacuum dried at 80 ° C, and the dried precipitate was ground to obtain rare earth-doped graphene.

[0033] The calcium sulfate whiskers were added into a 5% by mass γ-aminopropyltriethoxysilane ethanol solution so that the mass ratio of the calcium sulfate whiskers to the γ-aminopropyltriethoxysilane was 10:1. The mixture was stirred at 500 rpm for 3 hours. After being collected by centrifugation, the mixture was washed three times with anhydrous ethanol and dried in vacuo at 80°C to obtain pretreated calcium sulfate whiskers.

[0034] 10.59 kg of aniline was dissolved in 20 L of 1 mol / L hydrochloric acid aqueous solution to obtain an aniline solution; 17.65 kg of pretreated calcium sulfate whiskers were added to the aniline solution, and 1.76 kg of rare earth-doped graphene was added to obtain a mixed solution, and an azobisisobutyronitrile aqueous solution containing 0.2 kg of azobisisobutyronitrile was added to the mixed solution under ice-water bath conditions, and the addition was completed within 1 hour. After the addition was completed, the reaction was stirred at a speed of 200 rpm under ice-water bath conditions for 4 hours, and the product was centrifuged to obtain the product, and the product was washed three times with deionized water and ethanol respectively, and the washed product was dried in an oven at 80° C. to obtain modified barium sulfate whiskers.

[0035] Preparation of corrosion-resistant bulk bags 20kg of recycled pellets, 50kg of corrosion-resistant modified polypropylene and 10kg of modified calcium sulfate whiskers are stirred and mixed at a speed of 500rpm for 5min, 3kg of plasticizer, 0.5kg of antioxidant and 1.5kg of lubricant are added, the speed is increased to 1200rpm and stirred and mixed for 10min to obtain a mixture; the mixture is added to a single-screw extruder for granulation, the granulation temperature is 170-190℃ in zone 1, 190-210℃ in zone 2, 210-230℃ in zone 3, and the speed is 150rpm to obtain a mixed pellet; the mixed pellet is added to a flat wire extruder, extruded into a sheet, the thickness of the sheet is controlled to be 0.3mm, the sheet is cooled in 20℃ water, and after cooling, it is cut into flat wires with a width of 2mm, the flat wire is stretched and shaped at 120℃, the stretching multiple is 5 times, and after stretching, it is heat-set at 150℃ to obtain a shaped flat wire; the shaped flat wire is woven on a braiding machine to obtain a main material layer.

[0036] The adhesive is applied to the bonding surface of the main material layer and the lining layer, and after extrusion bonding, it is cured at 80°C for 24 hours to obtain a bonding material; the bonding material is cut and sewn to obtain a corrosion-resistant container bag.

[0037] Example 2 Preparation of recycled pellets: The recycled bulk bags are sorted and selected, and then cut and crushed after removing impurities to obtain bulk bag fragments; the bulk bag fragments are soaked and washed in water for 1 hour, and then centrifuged and dehydrated for 15 minutes at a centrifugal speed of 1200rpm. After centrifugation, they are dried at 60°C until the water content is less than 0.5% to obtain dry bulk bag fragments; the dried bulk bag fragments are conveyed to a twin-screw extruder for extrusion and melting, and the temperatures of each section in the extruder are 160-180°C for zone one, 180-200°C for zone two, 200-220°C for zone three, and 220-230°C for zone four. -240℃, filter through a 100-mesh stainless steel filter while extruding and melting, and after filtration, use an underwater pelletizer to granulate and form, the water temperature of the pelletizer is 30℃, and preliminary recycled pellets are obtained; the preliminary recycled pellets and ethylene-vinyl acetate copolymer are added into an internal mixer in a mass ratio of 4:1 for mixing and internal mixing, the temperature of the internal mixer is 200℃, the internal mixing time is 10min, the rotation speed is 50rpm, the material after internal mixing is extruded and granulated through a single screw extruder, the extruder temperature is 170-190℃, and recycled pellets are obtained.

[0038] Preparation of corrosion-resistant modified polypropylene 78.13 kg of polypropylene, 2.34 kg of maleic anhydride and 19.53 kg of trifluoropropylmethylcyclotrisiloxane were premixed in a high-speed mixer for 10 minutes at a premixing speed of 1000 rpm to obtain a premix; under a nitrogen atmosphere, the premix was added to an internal mixer, preheated at 180° C. at a speed of 50 rpm for 10 minutes, 0.5 kg of initiator was added, internal mixing was performed for 20 minutes, and the material was discharged to obtain corrosion-resistant modified polypropylene.

[0039] Preparation of modified barium sulfate whiskers 2 kg of graphene oxide was dispersed in 5 L of deionized water, and a graphene dispersion was obtained after ultrasonic treatment for 30 min; 0.1 kg of lanthanum nitrate, 0.05 kg of cerium nitrate and 0.05 kg of yttrium nitrate were dissolved in 1 L of deionized water to obtain a rare earth mixed solution; under the condition of stirring at a speed of 200 rpm, the rare earth mixed solution was added to the graphene dispersion, and the addition was completed within 1 hour. After the addition was completed, a mixed dispersion was obtained; 0.15 kg of ascorbic acid was added to the mixed dispersion, the temperature was raised to 100 ° C and stirred at a speed of 200 rpm for 4 hours, after cooling to below 30 ° C, centrifuged to obtain a precipitate, the precipitate was washed three times with deionized water and ethanol respectively, the washed precipitate was vacuum dried at 80 ° C, and the dried precipitate was ground to obtain rare earth-doped graphene.

[0040] The calcium sulfate whiskers were added into a 5% by mass γ-aminopropyltriethoxysilane ethanol solution so that the mass ratio of the calcium sulfate whiskers to the γ-aminopropyltriethoxysilane was 10:1. The mixture was stirred at 500 rpm for 3 hours. After being collected by centrifugation, the mixture was washed three times with anhydrous ethanol and dried in vacuo at 80°C to obtain pretreated calcium sulfate whiskers.

[0041] 12.63 kg of aniline was dissolved in 20 L of 1 mol / L hydrochloric acid aqueous solution to obtain an aniline solution; 15.79 kg of pretreated calcium sulfate whiskers were added to the aniline solution, and 1.58 kg of rare earth-doped graphene was added to obtain a mixed solution, and an azobisisobutyronitrile aqueous solution containing 0.2 kg of azobisisobutyronitrile was added to the mixed solution under ice-water bath conditions, and the addition was completed within 1 hour. After the addition was completed, the reaction was stirred at a speed of 200 rpm under ice-water bath conditions for 4 hours, and the product was centrifuged to obtain the product, and the product was washed three times with deionized water and ethanol respectively, and the washed product was dried in an oven at 80° C. to obtain modified barium sulfate whiskers.

[0042] Preparation of corrosion-resistant bulk bags 30kg of recycled pellets, 70kg of corrosion-resistant modified polypropylene and 20kg of modified calcium sulfate whiskers are stirred and mixed at a speed of 500rpm for 5min, 6kg of plasticizer, 1.5kg of antioxidant and 2.5kg of lubricant are added, the speed is increased to 1200rpm and stirred and mixed for 10min to obtain a mixture; the mixture is added to a single-screw extruder for granulation, the granulation temperature is 170-190℃ in zone 1, 190-210℃ in zone 2, 210-230℃ in zone 3, and the speed is 150rpm to obtain a mixed pellet; the mixed pellet is added to a flat wire extruder, extruded into a sheet, the thickness of the sheet is controlled to be 0.3mm, the sheet is cooled in 20℃ water, and after cooling, it is cut into flat wires with a width of 2mm, the flat wire is stretched and shaped at 120℃, the stretching multiple is 5 times, and after stretching, it is heat-set at 150℃ to obtain a shaped flat wire; the shaped flat wire is woven on a braiding machine to obtain a main material layer.

[0043] The adhesive is applied to the bonding surface of the main material layer and the lining layer, and after extrusion bonding, it is cured at 80°C for 24 hours to obtain a bonding material; the bonding material is cut and sewn to obtain a corrosion-resistant container bag.

[0044] Example 3 Preparation of recycled pellets: The recycled bulk bags are sorted and selected, and then cut and crushed after removing impurities to obtain bulk bag fragments; the bulk bag fragments are soaked and washed in water for 1 hour, and then centrifuged and dehydrated for 15 minutes at a centrifugal speed of 1200rpm. After centrifugation, they are dried at 60°C until the water content is less than 0.5% to obtain dry bulk bag fragments; the dried bulk bag fragments are conveyed to a twin-screw extruder for extrusion and melting, and the temperatures of each section in the extruder are 160-180°C for zone one, 180-200°C for zone two, 200-220°C for zone three, and 220-230°C for zone four. -240℃, filter through a 100-mesh stainless steel filter while extruding and melting, and after filtration, use an underwater pelletizer to granulate and form, the water temperature of the pelletizer is 30℃, and preliminary recycled pellets are obtained; the preliminary recycled pellets and ethylene-vinyl acetate copolymer are added into an internal mixer in a mass ratio of 4:1 for mixing and internal mixing, the temperature of the internal mixer is 200℃, the internal mixing time is 10min, the rotation speed is 50rpm, the material after internal mixing is extruded and granulated through a single screw extruder, the extruder temperature is 170-190℃, and recycled pellets are obtained.

[0045] Preparation of corrosion-resistant modified polypropylene 81.3 kg of polypropylene, 2.44 kg of maleic anhydride and 16.26 kg of trifluoropropylmethylcyclotrisiloxane were premixed in a high-speed mixer for 10 minutes at a premixing speed of 1000 rpm to obtain a premix; under a nitrogen atmosphere, the premix was added to an internal mixer, preheated at 180° C. at a speed of 50 rpm for 10 minutes, 0.5 kg of initiator was added, internal mixing was performed for 20 minutes, and the material was discharged to obtain corrosion-resistant modified polypropylene.

[0046] Preparation of modified barium sulfate whiskers 2 kg of graphene oxide was dispersed in 5 L of deionized water, and a graphene dispersion was obtained after ultrasonic treatment for 30 min; 0.1 kg of lanthanum nitrate, 0.05 kg of cerium nitrate and 0.05 kg of yttrium nitrate were dissolved in 1 L of deionized water to obtain a rare earth mixed solution; under the condition of stirring at a speed of 200 rpm, the rare earth mixed solution was added to the graphene dispersion, and the addition was completed within 1 hour. After the addition was completed, a mixed dispersion was obtained; 0.15 kg of ascorbic acid was added to the mixed dispersion, the temperature was raised to 100 ° C and stirred at a speed of 200 rpm for 4 hours, after cooling to below 30 ° C, centrifuged to obtain a precipitate, the precipitate was washed three times with deionized water and ethanol respectively, the washed precipitate was vacuum dried at 80 ° C, and the dried precipitate was ground to obtain rare earth-doped graphene.

[0047] The calcium sulfate whiskers were added into a 5% by mass γ-aminopropyltriethoxysilane ethanol solution so that the mass ratio of the calcium sulfate whiskers to the γ-aminopropyltriethoxysilane was 10:1. The mixture was stirred at 500 rpm for 3 hours. After being collected by centrifugation, the mixture was washed three times with anhydrous ethanol and dried in vacuo at 80°C to obtain pretreated calcium sulfate whiskers.

[0048] 11.66 kg of aniline was dissolved in 20 L of 1 mol / L hydrochloric acid aqueous solution to obtain an aniline solution; 16.67 kg of pretreated calcium sulfate whiskers were added to the aniline solution, and 1.67 kg of rare earth-doped graphene was added to obtain a mixed solution, and an azobisisobutyronitrile aqueous solution containing 0.2 kg of azobisisobutyronitrile was added to the mixed solution under ice-water bath conditions, and the addition was completed within 1 hour. After the addition was completed, the reaction was stirred at a speed of 200 rpm under ice-water bath conditions for 4 hours, and the product was centrifuged to obtain the product, and the product was washed three times with deionized water and ethanol respectively, and the washed product was dried in an oven at 80° C. to obtain modified barium sulfate whiskers.

[0049] Preparation of corrosion-resistant bulk bags 25kg of recycled pellets, 60kg of corrosion-resistant modified polypropylene and 15kg of modified calcium sulfate whiskers are stirred and mixed at a speed of 500rpm for 5min, 4.5kg of plasticizer, 1kg of antioxidant and 2kg of lubricant are added, the speed is increased to 1200rpm and stirred and mixed for 10min to obtain a mixture; the mixture is added to a single-screw extruder for granulation, the granulation temperature is 170-190℃ in zone 1, 190-210℃ in zone 2, 210-230℃ in zone 3, and the speed is 150rpm to obtain a mixed pellet; the mixed pellet is added to a flat wire extruder, extruded into a sheet, the thickness of the sheet is controlled to be 0.3mm, the sheet is cooled in 20℃ water, and after cooling, it is cut into flat wires with a width of 2mm, the flat wire is stretched and shaped at 120℃, the stretching multiple is 5 times, and after stretching, it is heat-set at 150℃ to obtain a shaped flat wire; the shaped flat wire is woven on a braiding machine to obtain a main material layer.

[0050] The adhesive is applied to the bonding surface of the main material layer and the lining layer, and after extrusion bonding, it is cured at 80°C for 24 hours to obtain a bonding material; the bonding material is cut and sewn to obtain a corrosion-resistant container bag.

[0051] Example 4 Example 4 is based on Example 3. The only difference between Example 4 and Example 3 is that no ethylene-vinyl acetate copolymer is added when preparing the recycled pellets in Example 4.

[0052] Example 5 Example 5 is based on Example 3. The only difference between Example 5 and Example 3 is that in Example 5, the amount of polypropylene used is 88.5 kg, the amount of maleic anhydride used is 2.65 kg, and the amount of trifluoropropylmethylcyclotrisiloxane used is 8.85 kg.

[0053] Example 6 Example 6 is based on Example 3. The only difference between Example 6 and Example 3 is that in Example 6, the amount of polypropylene used is 69.93 kg, the amount of maleic anhydride used is 2.1 kg, and the amount of trifluoropropylmethylcyclotrisiloxane used is 27.97 kg.

[0054] Example 7 Example 7 is based on Example 3. The only difference between Example 7 and Example 3 is that maleic anhydride is not added when preparing the corrosion-resistant modified polypropylene in Example 7.

[0055] Example 8 Example 8 is based on Example 3. The only difference between Example 8 and Example 3 is that yttrium nitrate is not added when preparing rare earth-doped graphene in Example 8.

[0056] Example 9 Example 9 is based on Example 3. The only difference between Example 9 and Example 3 is that lanthanum nitrate and cerium nitrate are not added when preparing rare earth-doped yttrium nitrate in Example 9.

[0057] Example 10 Example 10 is based on Example 3. The only difference between Example 10 and Example 3 is that in Example 10, the amount of pretreated calcium sulfate whiskers is 20 kg, the amount of rare earth-doped graphene is 2 kg, and the amount of aniline is 8 kg.

[0058] Embodiment 11 Example 11 is based on Example 3. The only difference between Example 11 and Example 3 is that in Example 11, the amount of pretreated calcium sulfate whiskers is 14.28 kg, the amount of rare earth-doped graphene is 1.44 kg, and the amount of aniline is 14.28 kg.

[0059] Example 12 Example 12 is based on Example 3. The only difference between Example 12 and Example 3 is that in Example 12, rare earth-doped graphene is replaced with graphene oxide when preparing modified calcium sulfate whiskers.

[0060] Embodiment 13 Example 13 is based on Example 3. The only difference between Example 13 and Example 3 is that no rare earth-doped graphene is added when preparing modified calcium sulfate whiskers in Example 13.

[0061] Comparative Example 1 Comparative Example 1 is based on Example 3, and the only difference between Comparative Example 1 and Example 3 is that in Comparative Example 1, the corrosion-resistant modified polypropylene is replaced by polypropylene.

[0062] Comparative Example 2 Comparative Example 2 is based on Example 3, and the only difference between Comparative Example 2 and Example 3 is that in Comparative Example 2, the modified calcium sulfate whiskers are replaced by calcium sulfate whiskers.

[0063] Performance testing (1) Select GB / T 10454-2000 Container Bag as the standard to test the tensile strength of the sample. Prepare three samples for each sample, take the average value after measurement, and record the results in Table 1.

[0064] (2) Corrosion resistance test: The samples were placed in a 5% by mass sulfuric acid aqueous solution and a 5% by mass sodium hydroxide aqueous solution, respectively, and the changes on the sample surface were observed and the time when the changes occurred were recorded. The results are recorded in Table 1.

[0065] Table 1 Test results of tensile strength and corrosion resistance of bulk bags It can be seen from Table 1 that the tensile strength of Examples 1-3 is greater than 1846N in the transverse direction and greater than 1842N in the longitudinal direction, the acid corrosion resistance time is greater than 194h, and the alkali corrosion resistance time is greater than 189h, which shows that the container bags prepared in this application have high strength and good corrosion resistance.

[0066] It can be seen from Table 1 that the only difference between Example 4 and Example 3 is that no ethylene-vinyl acetate copolymer is added when preparing the recycled pellets in Example 4. Compared with Example 3, the tensile strength and corrosion resistance of Example 4 are reduced. This is because without adding ethylene-vinyl acetate copolymer, the compatibility of the recycled pellets with other components in the main material layer is reduced, the stability of the material is deteriorated, and thus the corrosion resistance and tensile strength are reduced.

[0067] As can be seen from Table 1, the only difference between Examples 5-7 and Example 3 is that in Example 5, the mass ratio of polypropylene, maleic anhydride and trifluoropropylmethylcyclotrisiloxane is 1:0.03:0.1, in Example 6, the mass ratio of polypropylene, maleic anhydride and trifluoropropylmethylcyclotrisiloxane is 1:0.03:0.4, and maleic anhydride is not added when preparing corrosion-resistant modified polypropylene in Example 7. Compared with Example 3, the corrosion resistance and tensile strength of Examples 5-7 are reduced; this is because the ratio of the components in the corrosion-resistant modified polypropylene is destroyed, too little siloxane modification effect is limited, and too much siloxane will destroy the original force and stacking structure between the molecular chains, affecting its stability; in the absence of maleic anhydride, there is a lack of bridging between siloxane and polypropylene, the compatibility is reduced, and thus the corrosion resistance and tensile strength are reduced.

[0068] As shown in Table 1, the only difference between Examples 8-13 and Example 3 is that: in Example 8, yttrium nitrate is not added when preparing rare earth-doped graphene, in Example 9, lanthanum nitrate and cerium nitrate are not added when preparing rare earth-doped yttrium nitrate, in Example 10, the mass ratio of pretreated calcium sulfate whiskers, rare earth-doped graphene and aniline is 1:0.1:0.4, in Example 11, the mass ratio of pretreated calcium sulfate whiskers, rare earth-doped graphene and aniline is 1:0.1:1, in Example 12, rare earth-doped graphene is replaced by graphene oxide when preparing modified calcium sulfate whiskers, and in Example 13, modified sulfur is prepared. No rare earth-doped graphene is added when preparing modified calcium sulfate whiskers. Compared with Example 3, the tensile strength and corrosion resistance of Examples 8-13 are reduced. This is because if the doping types of rare earth elements in the rare earth-doped graphene are reduced, the synergistic effect between the various rare earth elements will be affected. If the ratio of the components in the modified calcium sulfate whiskers is destroyed, too much or too little aniline will affect the dispersibility and compatibility of the modified calcium sulfate whiskers. If rare earth elements are not used to dope graphene oxide or rare earth-doped graphene is not added directly, the performance will be further reduced, thereby reducing the corrosion resistance and tensile strength.

[0069] It can be seen from Table 1 that the only difference between Comparative Example 1 and Example 3 is that the corrosion-resistant modified polypropylene is replaced by polypropylene in Comparative Example 1. Compared with Example 3, the corrosion resistance and tensile strength of Comparative Example 1 are reduced. This is because the polypropylene lacks modification treatment, the compatibility of the components in the container bag is reduced, the intermolecular interaction is weakened, and the stability is reduced, and the corrosion resistance and tensile strength are reduced.

[0070] As can be seen from Table 1, the difference between Comparative Example 2 and Example 3 is that the modified calcium sulfate whisker is replaced by calcium sulfate whisker in Comparative Example 2, and the corrosion resistance and tensile strength of Comparative Example 2 are reduced compared with Example 3; this is because the calcium sulfate whisker lacks modification treatment, the dispersibility and compatibility are reduced, and the synergistic effect between the components is weakened, thereby reducing the corrosion resistance and tensile strength.

[0071] This specific embodiment is only an explanation of the present application, and it is not a limitation of the present application. Through the above description, relevant staff can make various changes and modifications without deviating from the technical idea of ​​the present application. The technical scope of the present application is not limited to the content in the specification, and its technical scope must be determined according to the scope of the claims.

Claims

1. A corrosion-resistant container bag, characterized by: It comprises a main material layer and an inner lining layer, wherein the raw material for preparing the inner lining layer comprises polytetrafluoroethylene, and the raw material for preparing the main material layer comprises the following components in parts by weight: Recycled granules 20-30 parts Corrosion-resistant modified polypropylene 50-70 parts Modified calcium sulfate whisker 10-20 parts Plasticizer 3-6 parts Antioxidant 0.5-1.5 parts Lubricant 1.5-2.5 parts.

2. The corrosion-resistant container bag according to claim 1, characterized in that: The raw materials for preparing the recycled granules include waste container bags and ethylene-vinyl acetate copolymer.

3. A corrosion-resistant container bag according to claim 2, characterized in that: The regenerated pellets are prepared by the following steps: The recycled bulk bags are sorted and selected, and the impurities are removed and then cut and crushed to obtain bulk bag fragments; the bulk bag fragments are washed and dehydrated, and then dried to obtain dry bulk bag fragments; the dry bulk bag fragments are extruded and melted, and filtered while being extruded and melted, and then granulated and formed to obtain preliminary recycled pellets; the preliminary recycled pellets and ethylene-vinyl acetate copolymer are mixed and kneaded, and then extruded and granulated to obtain recycled pellets.

4. The corrosion-resistant container bag according to claim 1, characterized in that: The raw materials for preparing the corrosion-resistant modified polypropylene include polypropylene body, maleic anhydride and trifluoropropylmethylcyclotrisiloxane.

5. The corrosion-resistant container bag according to claim 4, characterized in that: The mass ratio of the polypropylene body, maleic anhydride and trifluoropropylmethylcyclotrisiloxane is 1:0.03:(0.15-0.25).

6. The corrosion-resistant container bag according to claim 1, characterized in that: The raw materials for preparing the modified calcium sulfate whisker include pretreated calcium sulfate whisker, rare earth-doped graphene and aniline.

7. The corrosion-resistant container bag according to claim 6, characterized in that: The raw materials for preparing the rare earth-doped graphene include graphene oxide, lanthanum nitrate, cerium nitrate and yttrium nitrate.

8. The corrosion-resistant container bag according to claim 7, characterized in that: The rare earth-doped graphene is prepared by the following steps: The graphene oxide is dispersed in water, and a graphene dispersion is obtained after ultrasonic treatment; lanthanum nitrate, cerium nitrate and yttrium nitrate are dissolved in water to obtain a rare earth mixed liquid; under stirring conditions, the rare earth mixed liquid is added to the graphene dispersion to obtain a mixed dispersion; ascorbic acid is added to the mixed dispersion, the temperature is raised and stirred for reaction, after cooling, centrifugation is performed to obtain a precipitate, the precipitate is washed three times with water and ethanol respectively, the washed precipitate is vacuum dried, and the dried precipitate is ground to obtain rare earth-doped graphene.

9. The corrosion-resistant container bag according to claim 8, characterized in that: The mass ratio of the pretreated calcium sulfate whisker, rare earth-doped graphene and aniline is 1:0.1:(0.6-0.8).

10. A process for preparing a corrosion-resistant container bag as claimed in any one of claims 1 to 9, characterized in that: The following steps are involved: The recycled pellets, corrosion-resistant modified polypropylene and modified calcium sulfate whiskers are stirred and mixed, a plasticizer, an antioxidant and a lubricant are added, the speed is increased and the mixture is stirred and mixed to obtain a mixture; the mixture is granulated to obtain a mixed pellet; the mixed pellet is extruded into a sheet, cooled in water, and cut into flat wires after cooling, and the flat wires are stretched and heat-set to obtain a set flat wire; the set flat wires are woven to obtain a main material layer; The adhesive is applied to the bonding surface of the main material layer and the lining layer, and after extrusion bonding, the bonding is heated and cured to obtain a bonding material; the bonding material is cut and sewn to obtain a corrosion-resistant container bag.